Lohnspreizung und Effizienz - Ekkehart Schlicht (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2008)
– Wage Dispersion and Efficiency. It is often assumed that markets generate efficient allocations, but these are not necessarily fair. The widening of wage differentials that is currently observed is interpreted in this manner: Skill-biased technological progress increases demand for skilled work and makes unskilled labor redundant. Increasing wage dispersion is seen as a market response to an increased scarcity of skilled workers. While wage differentials are widening, we observe at the same time increasing over-qualification in all segments of the labor market. This suggests an increasing abundance of skilled workers, rather than shortage. This paper suggest an explanation for the joint occurrence of wage dispersion and over-qualification. Wage dispersion is brought about by the wage-setting policies of firms that respond to an increased importance of skill differences among workers. The widening wage differentials render the acquisition of skills more rewarding. As a result, wage dispersion and over-qualification increase together. Both are inefficient. Policies that bring wage differentials closer to compensating differentials will increase both efficiency and fairness, quite in line with the classical position taken by Adam Smith on these issues.
urn:nbn:de:bvb:19-epub-2117-1
Keywords: D43; J31; J63; 330; Wage structure; wage dispersion; wage compression; over-qualification; over-education; fairness; efficiency; wage competition; job competition; Reder competition; Adam Smith; Alfred Marshall; compensating differentials; job rents; skill-biased technological progess; heterogeneity-biased technological progress; Lohnstruktur; Lohnspreizung; Überqualifikation; Lohnkompression; Gerechtigkeit; Effizienz; Reder-Wettbewerb; Lohnwettbewerb; Qualifikationswettbewerb; kompensierende Lohndifferentiale; Jobrenten; Adam Smith; Alfred Marshall; skill-biased technological progess; heterogeneity-biased technological progress; Lohnstruktur; Unterbeschäftigung; Arbeitsmarkt; Qualifikation; Lohnbildung; Wettbewerb; Wirtschaftliche Effizienz; Deutschland